A Systematic Review of Cost-Effectiveness Studies Reporting Cost-per-DALY Averted. - Peter J Neumann; Teja Thorat; Yue Zhong; Jordan Anderson; Megan Farquhar; Mark Salem; Eileen Sandberg; Cayla J Saret; Colby Wilkinson; Joshua T Cohen (PLoS ONE)
Introduction Calculating the cost per disability-adjusted life years (DALYs) averted associated with interventions is an increasing popular means of assessing the cost-effectiveness of strategies to improve population health. However, there has been no systematic attempt to characterize the literature and its evolution. Methods We conducted a systematic review of cost-effectiveness studies reporting cost-per-DALY averted from 2000 through 2015. We developed the Global Health Cost-Effectiveness Analysis (GHCEA) Registry, a repository of English-language cost-per-DALY averted studies indexed in PubMed. To identify candidate studies, we searched PubMed for articles with titles or abstracts containing the phrases "disability-adjusted" or "DALY". Two reviewers with training in health economics independently reviewed each article selected in our abstract review, gathering information using a standardized data collection form. We summarized descriptive characteristics on study methodology: e.g., intervention type, country of study, study funder, study perspective, along with methodological and reporting practices over two time periods: 2000-2009 and 2010-2015. We analyzed the types of costs included in analyses, the study quality on a scale from 1 (low) to 7 (high), and examined the correlation between diseases researched and the burden of disease in different world regions. Results We identified 479 cost-per-DALY averted studies published from 2000 through 2015. Studies from Sub-Saharan Africa comprised the largest portion of published studies. The disease areas most commonly studied were communicable, maternal, neonatal, and nutritional disorders (67%), followed by non-communicable diseases (28%). A high proportion of studies evaluated primary prevention strategies (59%). Pharmaceutical interventions were commonly assessed (32%) followed by immunizations (28%). Adherence to good practices for conducting and reporting cost-effectiveness analysis varied considerably. Studies mainly included formal healthcare sector costs. A large number of the studies in Sub-Saharan Africa addressed high-burden conditions such as HIV/AIDS, tuberculosis, neglected tropical diseases and malaria, and diarrhea, lower respiratory infections, meningitis, and other common infectious diseases. Conclusion The Global Health Cost-Effectiveness Analysis Registry reveals a growing and diverse field of cost-per-DALY averted studies. However, study methods and reporting practices have varied substantially.